2013
DOI: 10.1177/0021909613510246
|View full text |Cite
|
Sign up to set email alerts
|

The Toponymic Inscription Problematic in Urban Sub-Saharan Africa: From Colonial to Postcolonial Times

Abstract: We examine a variety of problems relating to toponymic inscription processes in urban sub-Saharan Africa. The objective is to promote understanding of: the origins, evolution, nature, extent and social implications of these problems in an era of globalization; the vocabularies of built space; and the navigation techniques of inhabitants of supposedly nondescript built space in this region. We employed primary data based on in situ experiences and secondary data from published and unpublished documents. We foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 20 publications
0
24
0
1
Order By: Relevance
“…The toponymic nomenclature imposed on African built space by colonial authorities and agents of Western civilization generously draws appellations from Eurocentric lexical vocabularies. Although the colonial origin of this proclivity is well-established (Bigon and Njoh, 2015), its raison d’être is not. Why did colonial authorities, and agents of Western civilization after them, draw from Eurocentric vocabularies of spatiality?…”
Section: Introductionmentioning
confidence: 99%
“…The toponymic nomenclature imposed on African built space by colonial authorities and agents of Western civilization generously draws appellations from Eurocentric lexical vocabularies. Although the colonial origin of this proclivity is well-established (Bigon and Njoh, 2015), its raison d’être is not. Why did colonial authorities, and agents of Western civilization after them, draw from Eurocentric vocabularies of spatiality?…”
Section: Introductionmentioning
confidence: 99%
“…Bigon and Njoh further assert that, in colonial contexts, place-naming reflected the racial hierarchical structure and spatial segregation created by the Europeans, leading to toponymic ambiguity in post-independence cities [19]. Ndletyana, in his analysis of the South African toponymic struggle, states that colonial toponyms 'reflected the cultural prejudice of colonial settlers .…”
Section: Critical Toponymy: a Theoretical Backgroundmentioning
confidence: 99%
“…While S'ncamtho toponyms may be seen by some as ephemeral and passing, studies have actually shown that some elements of slang last long enough to influence language change. Bigon and Njoh (2015) aver that the distinction between conventional and unconventional in African urban toponymy is not clearly determined as the colonisers supplanted toponyms in the colonies replacing them with their own culture, and after independence the colonised undertook name changes creating ambiguities. This study argues that S'ncamtho toponyms are an expression of urban culture and history, and may, in fact, create ambiguities.…”
Section: Characterisation and Social Impact Of Urban Youth Languages mentioning
confidence: 99%